Globalization and Decentralization of Management: A Study of the Feasibility of Application of School-Based Management in Iran’s Secondary Schools (Alberta Journal of Educational Research, 2006)
The main purpose of this study was to recognize the critical barriers of school-based management in Iran in general, and in public secondary schools of Ahvaz in particular. The subject is addressed with Lawler’s (1992) theory and those of other researchers in mind. The main questions are: What are the characteristics of the new system of school-based management in Iran’s secondary schools? How much do the secondary school principals, teachers, and local education authorities know about school-based management? To what extent do they agree with the application of school-based management? To what extent do they believe that school-based management is feasible for secondary schools? And what barriers hinder successful implementation of school-based management in Iran? Quantitative (questionnaire) and qualitative (interviews) approaches were used for collecting data. Results are reported in detail. We conclude that the school-based management scheme is not developing well and needs to be reconsidered by education policymakers. Some suggestions are made to facilitate the implementation of school-based management in Ahvaz.